2003
DOI: 10.1046/j.1365-2672.2003.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabiosis of proteolytic moulds and Salmonella in raw, ripe tomatoes

Abstract: Aims: The aim of this study was to determine the survival and growth characteristics of Salmonella enterica in sound and chill‐injured tomatoes as influenced by co‐infection with proteolytic moulds. Methods and Results: Sound (not chill injured) raw, ripe tomatoes (Lycopersicon esculentum Mill. ‘Roma’) were inoculated with a five‐serotype mixture of S. enterica and/or Alternata alternata (two strains), Cladosporium herbarum and C. cladosporioides. Simultaneous and delayed (3 days) inoculation of tomatoes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…While BFIs are exploited for the production of certain foods, fungi and bacteria are also key food spoilage organisms; however, few studies have examined whether BFIs contribute to food spoilage, perhaps due to an emphasis on diagnostics/systematics and shelf life prediction within the food industry (327). Some studies have examined the potential of fungi to assist colonization by human-pathogenic bacteria; for example, spoilage fungi on tomatoes can promote Salmonella colonization, an effect which is believed to be due to their effect on pH (393,394). The presence of rhizonin toxins produced by endobacteria inhabiting Rhizopus microsporus is a critical cause of food spoilage due to their hepatotoxicity (296).…”
Section: Food Processingmentioning
confidence: 99%
“…While BFIs are exploited for the production of certain foods, fungi and bacteria are also key food spoilage organisms; however, few studies have examined whether BFIs contribute to food spoilage, perhaps due to an emphasis on diagnostics/systematics and shelf life prediction within the food industry (327). Some studies have examined the potential of fungi to assist colonization by human-pathogenic bacteria; for example, spoilage fungi on tomatoes can promote Salmonella colonization, an effect which is believed to be due to their effect on pH (393,394). The presence of rhizonin toxins produced by endobacteria inhabiting Rhizopus microsporus is a critical cause of food spoilage due to their hepatotoxicity (296).…”
Section: Food Processingmentioning
confidence: 99%
“…Surveys of commercial produce have indicated that there is an increased likelihood of finding Salmonella in association with tissue that is damaged by soft-rot pathogens when compared with healthy tissue (Brandl, 2008;Wells & Butterfield, 1997). Positive effects on human pathogen growth have also been observed with some fungal plant pathogens (Wade & Beuchat, 2003).…”
Section: Interactions Between the Human Pathogenic Bacteria And Othermentioning
confidence: 99%
“…Spoilage also had a positive effect on the colonization of endive leaves by Listeria monocytogenes (11), whereas the pathogen was inhibited strongly in potato tuber slices infected with Pseudomonas fluorescens and Pseudomonas viridiflava, possibly due to iron competition (12). Furthermore, it was reported previously that some plant-pathogenic fungi are more likely to increase the proliferation of human pathogens in infected fruit tissue by neutralizing the pH in the lesions and thereby enabling bacterial growth (13)(14)(15).…”
mentioning
confidence: 91%